Effects of Low-Dose Sacubitril/Valsartan on Different Stages of Cardiac Hypertrophy in Salt-Loaded Hypertensive Rats. Issue 5 (May 2019) - Hamano, Go; Yamamoto, Koichi; Takami, Yoichi; Takeshita, Hikari; Shimosato, Takashi; Moritani, Toshinori; Rakugi, Hiromi
Abstract : Background: Sacubitril/valsartan was shown to attenuate the development of cardiac hypertrophy with enhanced blood pressure reduction compared with valsartan alone in animal models. We investigated whether a low-dose sacubitril/valsartan has blood pressure–independent effects on cardiac hypertrophy and pulmonary edema using a rat model of hypertension and obesity. Methods and Results: In plan 1, male SHR/NDmcr-cp rats fed normal or phase-increased high salt were treated with vehicle, 6-mg/kg sacubitril/valsartan or 3-mg/kg valsartan, for 6 months. In plan 2, after high-salt loading for 6 months, drugs were administered for 4 months. Antihypertensive effects of the 2 drugs were similar during all study periods. In plan 1 with normal salt, there were no differences between treatments in the left ventricle weight/body weight (BW), or lung weight/BW as an index of cardiac hypertrophy or pulmonary edema, respectively. These indexes were smaller in high-salt-fed rats with sacubitril/valsartan than vehicle. In plan 2, both indexes did not differ between vehicle and sacubitril/valsartan. Ventricle weight/BW was lower in valsartan than sacubitril/valsartan. In plan 2, gene markers of cardiac dysfunction were upregulated by sacubitril/valsartan compared with the other groups. Conclusions: Low-dose sacubitril/valsartan may have different effects depending on the stage of cardiac hypertrophy in rats. Abstract : Supplemental Digital Content is Available in the Text.